2019
DOI: 10.1111/jnc.14648
|View full text |Cite
|
Sign up to set email alerts
|

G protein‐coupled estrogen receptor activates cell type‐specific signaling pathways in cortical cultures: relevance to the selective loss of astrocytes

Abstract: Selective activation of the G protein‐coupled estrogen receptor has been proposed to avoid some of the side effects elicited by the activation of classical estrogen receptors α and β. Although its contribution to neuroprotection triggered by estradiol in brain disorders has been explored, the results regarding ischemic stroke are contradictory, and currently, there is no consensus on the role that this receptor may play. The present study aimed to investigate the role of GPER in the ischemic insult. For that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 88 publications
(204 reference statements)
2
19
1
Order By: Relevance
“…Previous studies have shown that GPER is widely distributed in the brain (50,53,55,56,60,73). Indeed, GPER has been shown to be expressed by neurons, astrocytes and oligodendrocytes (56,57,59,(74)(75)(76)(77) and GPER immunoreactivity has been detected by electron microscopy in both neuronal and glial profiles in the hippocampus (59), which is consistent with the detection of GPER immunoreactivity in cells with either neuronal or glial morphology in our study. Furthermore, we have detected a punctiform pattern of immunoreactivity that is absent in the cell nucleus, in agreement with the reported subcellular localization of GPER, either in the plasma membrane or in the endoplasmic reticulum and Golgi apparatus (52,54,57,(78)(79)(80).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that GPER is widely distributed in the brain (50,53,55,56,60,73). Indeed, GPER has been shown to be expressed by neurons, astrocytes and oligodendrocytes (56,57,59,(74)(75)(76)(77) and GPER immunoreactivity has been detected by electron microscopy in both neuronal and glial profiles in the hippocampus (59), which is consistent with the detection of GPER immunoreactivity in cells with either neuronal or glial morphology in our study. Furthermore, we have detected a punctiform pattern of immunoreactivity that is absent in the cell nucleus, in agreement with the reported subcellular localization of GPER, either in the plasma membrane or in the endoplasmic reticulum and Golgi apparatus (52,54,57,(78)(79)(80).…”
Section: Discussionsupporting
confidence: 92%
“…Acute administration of E2 or GPER selective agonists STX or G-1, improved neuron survival rate by 40-45% compared to control in ovariectomized female rats (145). In contrast, G-1 promoted apoptosis of rat embryo cortical astrocytes exposed to oxygen and glucose deprivation, whereas the addition of the GPER antagonist G-15 suppressed this effect, suggesting a direct impact of GPER on the viability of cortical astrocytes (146). Interestingly, administration of G-1 counteracted iron-and ovariectomyinduced memory impairments in female rats (147).…”
Section: Gper In Nervous Systemmentioning
confidence: 94%
“…The experimental paradigm used in this study was based on previous reports from our group (Roque & Baltazar, 2017;Roque et al, 2018).…”
Section: Experimental Designmentioning
confidence: 99%
“…The cells used in the immunocytochemistry assays were cultured on dishes containing coverslips previously coated with polyd-lysine and were fixed immediately after the reperfusion period. All protocols were developed as previously described (Roque & Baltazar, 2017;Roque et al, 2018). Millipore; Cat# MAB3420, RRID:AB_94855) and rabbit anti-Synapsin I (1:4,000; Merck Millipore; Cat# AB1543P, RRID:AB_90757) were incubated for 48 hr at 4°C.…”
Section: Immunocytochemistry Assaymentioning
confidence: 99%
See 1 more Smart Citation